Performance of the Abbott RealTime MTB RIF/INH resistance assay when used to test Mycobacterium tuberculosis specimens from Bangladesh - Kostera, Joshua (Infect Drug Resist, 2018)
INTRODUCTION: The Abbott RealTime MTB RIF/INH Resistance Assay (RT MTB RIF/INH) is an assay for the detection of rifampicin (RIF)- and/or isoniazid (INH)-resistant Mycobacterium tuberculosis (MTB). The assay can be used to test sputum, bronchial alveolar lavage, and N-Acetyl-L-Cysteine (NALC)/NaOH pellets prepared from these samples. The assay can be used in direct testing mode, or in reflex mode following a MTB positive result produced by its companion assay, Abbott RT MTB. METHODS: In this study, the direct testing mode was used to test paired sputum and NALC/NaOH pellets prepared from sputum collected from Bangladesh TB patients. One hundred and thirty two paired samples were tested. RESULTS: The RT MTB RIF/INH inhibition rate was 0%. One hundred and twenty-two paired samples had results above the assay limit of detection and were analyzed by comparing with results from phenotypic drug sensitivity testing, GeneXpert MTB/RIF (Xpert), and MTBDR plus (Hain). RT MTB RIF/INH results were in good agreement with those of GeneXpert and Hain. CONCLUSION: The ability of this assay to detect RIF and INH resistance may contribute to the global control of multidrug resistant tuberculosis.